EVALUASI PENERAPAN AKUNTANSI PERSEDIAAN OBAT BERDASARKAN PSAK NO. 14 PADA PT. CEMPAKA INDAH MURNI MANADO - Hengkeng, Gleidys Audina; Pangemanan, Sifrid S.; Waronggan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Inventory is very important for the survival of the company, the company must be able to estimate the amount of inventory it has. This study aims to determine the analysis of the application of drug inventory accounting based on PSAK No.14 at PT. Cempaka Indah Murni Manado engaged in the distribution of medicines. The analytical method used in this research is a qualitative descriptive method then the conclusion of the recording method applied in recording merchandise inventory is a computerized perpetual method, while the inventory valuation method uses the FIFO (First In First Out) method. The company does not recognize the purchase costs and conversion costs, the company only recognizes other costs such as shipping costs / shipping costs, incoming transfers, and sales costs because the products sold at PT. Cempaka Indah Murni Manado was sent from the head office in Surabaya. The results showed that the application of accounting for drug supplies was carried out. PT. Cempaka Indah Murni Manado is not in accordance with PSAK No. 14.